Novel Concept for the Expansion of the Fibula Bone as an Autologous Bone Graft: Experimental Tests on an Animal Implant Prototype—In Memoriam Volker Buehren - Matthias Militz; Volker Buehren; Christoph Miethke; Carolin Gabler; Josephine Mauck; Wolfram Mittelmeier; Robert Bialas; Rainer Bader (Surgical Techniques Development, 2024)
The current reconstructive surgical procedures implemented after the resection of extended bone segments are associated with high complication rates and long-term treatments. By transplanting an autologous, vascularized and stabilized bone segment, these challenges can be managed. Thus, we propose a novel procedure to expand the currently available autologous bone grafts to the dimensions of the recipient bone using an implantable device. The objective of the present study was to characterize the feasibility of developing an implant prototype for fibula expansion in an in vitro model using a porcine fibula. A balloon catheter, as the part of the implant responsible for expansion, was proven to expand while being periodically filled with sodium chloride. Therefore, the expansion of the balloon catheter was analyzed in an experimental test setup with a 3D-printed porcine fibula with a closure film simulating callus formation to simulate the in vivo situation. Our experimental testing proved the successful expansion of the porcine fibula by the balloon catheter. Hence, the feasibility of the concept for subsequent animal testing was confirmed.